Cytocompatibility Evaluation of a Novel Series of PEG-Functionalized Lactide-Caprolactone Copolymer Biomaterials for Cardiovascular Applications - Pacharra, Sandra; McMahon, Seán; Duffy, Patrick; Basnett, Pooja; Yu, Wenfa; Seisel, Sabine; Stervbo, Ulrik; Babel, Nina; Roy, Ipsita; Viebahn, Richard; Wang, Wenxin; Salber, Jochen (Frontiers in Bioengineering and Biotechnology, 2020)
Although the use of bioresorbable materials in stent production is thought to improve long-term safety compared to their durable counterparts, a recent FDA report on the two-year follow-up of the first FDA-approved bioresorbable vascular stent showed an increased occurrence of major adverse cardiac events and thrombosis in comparison to the metallic control. In order to overcome the issues of first generation bioresorbable polymers, a series of polyethylene glycol-functionalized poly-L-lactide-co-ɛ-caprolactone copolymers with varying lactide-to-caprolactone content is developed using a novel one-step PEG-functionalization and copolymerization strategy. This approach represents a new facile way towards surface enhancement for cellular interaction, which is shown by screening these materials regarding their cyto- and hemocompatibility in terms of cytotoxicity, hemolysis, platelet adhesion, leucocyte activation and endothelial cell adhesion. By varying the lactide-to-caprolactone polymer composition, it is possible to gradually affect endothelial and platelet adhesion which allows fine-tuning of the biological response based on polymer chemistry. All polymers developed were non-cytotoxic, had acceptable leucocyte activation levels and presented non-hemolytic (< 2% hemolysis rate) behavior except for PLCL-PEG 55:45 which presented hemolysis rate of 2.5%±0.5. Water contact angles were reduced in the polymers containing PEG functionalization (PLLA-PEG: 69.8°±2.3, PCL-PEG: 61.2°±7.5) versus those without (PLLA: 79.5°±3.2, PCL: 76.4°±10.2) while the materials PCL-PEG550, PLCL-PEG550 90:10 and PLCL-PEG550 70:30 demonstrated best endothelial cell adhesion. PLLA-PEG550 and PLCL-PEG550 70:30 presented as best candidates for cardiovascular implant use from a cytocompatibility perspective across the spectrum of testing completed. Altogether, these polymers are excellent innovative materials suited for an application in stent manufacture due to the ease in translation of this one-step synthesis strategy to device production and their excellent in vitro cyto- and hemocompatibility.